Effect of Good Corporate Governance, Corporate Social Responsibility, and Intellectual Capital On The Profitability Of Islamic Commercial Banks - Silvia Nazma Zahira; Yayuk Sri Rahayu (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze the effect of Good Corporate Governance, Corporate Social Responsibility, andIntellectual Capital on the profitability of Islamic Commercial Banks in Indonesia. In facing increasingly intensecompetition in the Islamic banking industry, improvements in financial performance are not only determined byfinancial factors, but also by the quality of corporate governance, the implementation of social responsibility, and the management of intellectual capital. Therefore, this study examines the relationship among these variableswithin the context of Islamic banking. This research employs a quantitative approach using panel data analysis methods. The data used are secondary data obtained from the annual financial reports of Islamic CommercialBanks published by the Financial Services Authority during the 2020–2024 period. The analysis was conducted using panel data regression with the selection of the most appropriate model to examine the relationships among the research variables. The results indicate that Good Corporate Governance does not have a significant effect on profitability, while Corporate Social Responsibility and Intellectual Capital have a significant effect on the profitability of Islamic Commercial Banks. These findings suggest that aspects of social responsibility and intellectual capital management play an important role in enhancing the financial performance of Islamicbanking institutions.